2020
DOI: 10.3390/ijms21186623
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis of Hodgkin Lymphoma: Past, Present, Future

Abstract: Our understanding of the tumorigenesis of classical Hodgkin lymphoma (cHL) and the formation of Reed–Sternberg cells (RS-cells) has evolved drastically in the last decades. More recently, a better characterization of the signaling pathways and the cellular interactions at play have paved the way for new targeted therapy in the hopes of improving outcomes. However, important gaps in knowledge remain that may hold the key for significant changes of paradigm in this lymphoma. Here, we discuss the past, present, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 115 publications
0
9
0
Order By: Relevance
“…In addition, it has been reported that positivity of EBER-ISH is associated with a high frequency of extranodal involvement in patients with CHL ( 12 ). Reed-Sternberg cells and Hodgkin cells with a rich inflammatory background ensure their survival through the selective recruitment of cells in their microenvironment, constitutional activation of anti-apoptotic pathways, and elaborate evasion of the host immune system ( 13 ). As in the two previous cases ( 9 , 10 ), the present case developed at an advanced age.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that positivity of EBER-ISH is associated with a high frequency of extranodal involvement in patients with CHL ( 12 ). Reed-Sternberg cells and Hodgkin cells with a rich inflammatory background ensure their survival through the selective recruitment of cells in their microenvironment, constitutional activation of anti-apoptotic pathways, and elaborate evasion of the host immune system ( 13 ). As in the two previous cases ( 9 , 10 ), the present case developed at an advanced age.…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism how early clonal lymphoid precursors (14) are transformed to malignant HRS cells remains elusive. Recent studies show that telomere deprotection likely plays an important role in the evolution of H-cells to RS-cells (15). Disruption in the shelterin protein complex leads to telomere shortening, disorganized chromosome fusions, and ultimately the formation of multinucleated telomere-poor RS cells (Figure 1B).…”
Section: Hodgkin Lymphomamentioning
confidence: 96%
“…Finally, a specific NR organization is observed during the differentiation stages of mono-nuclear Hodgkin cells to multi-nucleated Reed-Sternberg cells in classical Hodgkin’s lymphoma ( Contu et al, 2018 ; Bienz et al, 2020 ). Impressive lamin A/C intranuclear septa are seen in bi- to multi-nucleated Reed-Sternberg (RS) cells, where lamin staining showed internal lamin A/C structures, subdividing the nuclei into two or more smaller compartments.…”
Section: Introductionmentioning
confidence: 99%